1980
DOI: 10.1007/bf02407162
|View full text |Cite
|
Sign up to set email alerts
|

Normal maturational changes in bone matrix, mineral, and crystal size in the rat

Abstract: Normal rat bone maturation has been studied using biochemical methods and hydrazine separation of matrix and mineral for X-ray diffraction. In the bone, the amount of mineral increases between 4 and 22 weeks of age, while in the matrix, the ratio of noncollagenous protein to collagen progressively decreases. In mineral, in the absence of serum ion changes, growth in mean crystal size appears to be the determinant of the changing ratios of calcium, magnesium, carbonate, and phosphorus, and of the increasing min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(65 citation statements)
references
References 31 publications
4
50
0
2
Order By: Relevance
“…FTIRM analysis also showed that the CO3:PO4 ratio in the medial side was significantly higher than the lateral side of the calcified cartilage and subchondral bone of Hartley strain guinea pigs. Several studies [7,13,22,23] have shown that the carbonate content of bone minerals varied with age. Increased carbonate content with aging is related to changes in the mineral crystallinity during maturation [7,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FTIRM analysis also showed that the CO3:PO4 ratio in the medial side was significantly higher than the lateral side of the calcified cartilage and subchondral bone of Hartley strain guinea pigs. Several studies [7,13,22,23] have shown that the carbonate content of bone minerals varied with age. Increased carbonate content with aging is related to changes in the mineral crystallinity during maturation [7,18].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies [7,13,22,23] have shown that the carbonate content of bone minerals varied with age. Increased carbonate content with aging is related to changes in the mineral crystallinity during maturation [7,18]. Rey et al [27][28][29] used Fourier transform infrared spectroscopy and demonstrated increased carbonate content in bone minerals with increased bone age.…”
Section: Discussionmentioning
confidence: 99%
“…The magnesium content of bone decreases with increasing age. Although this element can enter into the calcium phosphate apatites as a substitute for calcium, it has also been reported to attach to the surface of the crystals [74].…”
Section: Minor Elementsmentioning
confidence: 99%
“…For example, X-ray diffraction patterns of bones from animals of different age show that the reflections become sharper with age increasing (Meneghini et al 2003;Bilezikian et al 2008). This effect is more pronounced in the crystallographic a-axis [(310) reflections] as compared to the caxis [(002) reflections] (Burnell et al 1980;Weiner and Traub 1986). The most comprehensive report describing how normal human bone mineral changes in composition and crystal size as a function of age was based on X-ray diffraction analyses by Hanschin and Stern (Hanschin and Stern 1995), who examined 117 homogenized iliac crest biopsies from patients aged 0-95 years.…”
Section: Bonementioning
confidence: 99%